2021
DOI: 10.18203/2320-1770.ijrcog20215117
|View full text |Cite
|
Sign up to set email alerts
|

African traditional abdominal massage in pregnancy resulting in antepartum uterine rupture, abruptio placenta and foetal demise – a case report

Abstract: The practice of abdominal massage dates to years ago and associated with foetal and maternal morbidity and mortality when undertaken by untrained traditional birth attendants in our setting. We present a 30-year old G3P2+0 with uterine rupture and intra-uterine foetal death following abdominal massage. She was resuscitated and had emergency exploratory laparotomy and repair of uterine rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…It was reported as it may result in abruption placenta, uterine rupture, fetal morbidity, fetal mortality, maternal morbidity, and maternal mortality. 4,5 In this study, abdominal massage during pregnancy was reported to be one of the traditional practices which used to be more commonly applied and became limited to be practiced by few of mothers in recent times, comparable results were reported from Ethiopian studies done in Limu Genet, Debark, and Debretabor, where some mothers reported history of abdominal massage. 23,25,26 This might happen due to closeness in socio-demographic characteristics and social norms.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It was reported as it may result in abruption placenta, uterine rupture, fetal morbidity, fetal mortality, maternal morbidity, and maternal mortality. 4,5 In this study, abdominal massage during pregnancy was reported to be one of the traditional practices which used to be more commonly applied and became limited to be practiced by few of mothers in recent times, comparable results were reported from Ethiopian studies done in Limu Genet, Debark, and Debretabor, where some mothers reported history of abdominal massage. 23,25,26 This might happen due to closeness in socio-demographic characteristics and social norms.…”
Section: Discussionsupporting
confidence: 76%
“…There are studies which report as herbal medicines are not necessarily safe alternatives to conventional medicines during pregnancy because their constituents are likely to have pharmacological activity and they might possess toxic constituents. 4,28 Reports from Ghana and Asian countries have also indicated that pregnant mothers have culture of using herbal medicine. 29,30 Comparing with a study conducted in Gonder, where half of study participants reported utilization of herbal medicine, 24 our finding showed limited experience of using herbal medicine during pregnancy and child birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ethiopian women use traditional practices to terminate unwanted pregnancies, including abdominal massage, the use of herbs, and heavy physical exercise (Solomon & Tesfaye, 2022). There are studies showing that abdominal massages performed by non-specialists can cause fetal and maternal morbidity and mortality (Amadi et al, 2022; Banul & Halu, 2020). It is seen that the religious beliefs and attitudes of all participating Muslim Afghan women who wanted to continue pregnancy influenced this decision.…”
Section: Discussionmentioning
confidence: 99%